RELEVANSI PENDIDIKAN PANCASILA DALAM MEMBENTUK KARAKTER GENERASI MUDA: RELEVANSI PENDIDIKAN PANCASILA DALAM MEMBENTUK KARAKTER GENERASI MUDA - Julita Purnama Sari; Uut Utama Sari; Padhila Kalya Putri (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
The purpose of this paper is to examine the relevance of Pancasila Education in shaping the character of the young generation amid the rapid development of globalization. This study uses a normative method by collecting data from various sources. Pancasila Education plays an important role in shaping the character of the younger generation as the foundation of the Indonesian state. The values of Pancasila aim to instill a sense of responsibility, mutual cooperation, justice, and love for the homeland. Strengthening Pancasila values in education can help young people become individuals with noble character, broad insight, and the ability to maintain unity and harmony amid diversity. Therefore, the implementation of education based on Pancasila is crucial to creating a strong and competitive national character in the future.